2020
DOI: 10.1007/978-3-030-65965-3_22
|View full text |Cite
|
Sign up to set email alerts
|

Linking Heterogeneous Data for Food Security Prediction

Abstract: Identifying food insecurity situations timely and accurately is a complex challenge. To prevent food crisis and design appropriate interventions, several food security warning and monitoring systems are very active in food-insecure countries. However, the limited types of data selected and the limitations of data processing methods used make it difficult to apprehend food security in all its complexity. In this work, we propose models that aim to predict two key indicators of food security: the food consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Methods based on machine and deep learning approaches using heterogeneous data produce good results [16,4]. However, the results are challenging to explain [2].…”
Section: Using Textual Features To Explain Data and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods based on machine and deep learning approaches using heterogeneous data produce good results [16,4]. However, the results are challenging to explain [2].…”
Section: Using Textual Features To Explain Data and Resultsmentioning
confidence: 99%
“…Heterogeneous data can be used to predict prices and stock market trends [17,11], perform person identification [8], analyze food security [4], monitor health information [18], etc. Recently, different types of features, such as textual and visual content-related features, have been considered in fake news detection approaches [15,1].…”
Section: Integration Of Textual Features With Heterogeneous Datamentioning
confidence: 99%
“…The research by Foini et al (2023) demonstrated that precise forecasts of insufficient food consumption levels could be made up to 30 days into the future, thereby informing decisions regarding the allocation of need-based humanitarian assistance. However, Deléglise et al (2020) discovered that predicting food security indices is a challenging issue; their models did not exceed R 2 = 0.38 for the Household Dietary Diversity Score (HDDS) and R 2 = 0.35 for the Food Consumption Score (FCS).…”
Section: Discussionmentioning
confidence: 99%